A new paradigm for the management of essential vocal tremor with botulinum toxin. (1st April 2013) - Gurey, Lowell E.; Sinclair, Catherine F.; Blitzer, Andrew
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis 1) To clarify essential voice tremor (EVT) phenomenology; 2) To report a management paradigm for essential voice tremor using botulinum toxin. Study Design Retrospective analysis of prospectively collected data. Methods Phenomenology from patients diagnosed with EVT between April 1996 and March 2012 was recorded, charted, and analyzed. A paradigm for treatment of EVT using botulinum toxin based on individualized clinical findings is discussed. Results Sixteen patients were included. Fewer than 50% patients were responsive to centrally acting oral medications. Fifteen patients analyzed had horizontal laryngeal tremor and received botulinum toxin injections to bilateral thyroarytenoid muscles. Thirteen patients had a vertical laryngeal tremor, and these patients underwent additional strap muscle injections. All patients had symptomatic improvement with reduced tremor amplitude. Dose adjustments over time depended on degree of symptomatic improvement. Conclusions Management of essential voice tremor with botulinum toxin is optimized by individualizing treatment based on the tremor phenomenology observed during clinical examination. Level of Evidence 4. Laryngoscope, 123:2497–2501, 2013